2011
DOI: 10.1007/s00248-011-9812-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Deterioration of Artistic Tiles from the Façade of the Grande Albergo Ausonia & Hungaria (Venice, Italy)

Abstract: The Grande Albergo Ausonia & Hungaria (Venice Lido, Italy) has an Art Nouveau polychrome ceramic coating on its façade, which was restored in 2007. Soon after the conservation treatment, many tiles of the façade decoration showed coloured alterations putatively attributed to the presence of microbial communities. To confirm the presence of the biological deposit and the stratigraphy of the Hungaria tiles, stereomicroscope, optical and environmental scanning electron microscope observations were made. The chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…However, lead is toxic to living organisms and the presence of microbial growth on lead‐rich substrates could be unexpected. Yet, the analyzed tile panel was severely colonized, and other studies have shown that glazes can be colonized by dense biofilms whenever exposed to certain outdoor environments (Giacomucci et al ., ; Coutinho et al ., ). Specific environmental factors, such as cool temperatures, high relative humidity, moderate solar irradiance, shelter from direct rain and surrounding vegetation seem to allow the settlement of microorganisms on ceramic materials (Coutinho et al ., ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, lead is toxic to living organisms and the presence of microbial growth on lead‐rich substrates could be unexpected. Yet, the analyzed tile panel was severely colonized, and other studies have shown that glazes can be colonized by dense biofilms whenever exposed to certain outdoor environments (Giacomucci et al ., ; Coutinho et al ., ). Specific environmental factors, such as cool temperatures, high relative humidity, moderate solar irradiance, shelter from direct rain and surrounding vegetation seem to allow the settlement of microorganisms on ceramic materials (Coutinho et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Nonlichenized pigmented fungi were shown to colonize rock surfaces and restored glazed tiles (Gorbushina et al ., ; Diakumaku et al . ; Pitzurra et al ., ; Gorbushina and Broughton, ; Giacomucci et al ., ; Cutler et al ., ). Giacomucci et al .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this fungal genus in tiles has been mentioned before using a similar ''swab'' technique [29]. The obtained superficial contamination patterns could be related with the different environmental conditions as found by Giacomucci et al [7] for the microbial deterioration of artistic tiles, detecting bacteria, eukaryotic algae, and fungi in deteriorated tile samples.…”
Section: Surface Microbiotamentioning
confidence: 90%
“…Dissolution of ceramic matrix constituents tends to increase the capillary porosity of the tiles and consequently renders them more vulnerable to other forms of attack such as frost, wetting, and drying [3][4][5]. Moreover, the colonization of ceramic tiles by microorganisms may contribute to their deterioration [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Morphological studies of the film were carried out at different magnifications. To evaluate the D. desulfuricans capability to attach onto the paint surface, a DAPI staining of samples A and B was performed according to Giacomucci et al (2011). Epifluorescence observations were carried out with a Leica DM4000B digital epifluorescence microscope equipped with Cool-Snap CF camera (Photometrics, Roper Scientific) and pictures were acquired using RS Image ver.…”
Section: Stereomicroscope and Epifluorescence Microscope Observationsmentioning
confidence: 99%